Mechanisms and therapeutic effectiveness of pulsed electromagnetic field therapy in oncology. (17th October 2016) - Vadalà, Maria; Morales‐Medina, Julio Cesar; Vallelunga, Annamaria; Palmieri, Beniamino; Laurino, Carmen; Iannitti, Tommaso
Abstract: Cancer is one of the most common causes of death worldwide. Available treatments are associated with numerous side effects and only a low percentage of patients achieve complete remission. Therefore, there is a strong need for new therapeutic strategies. In this regard, pulsed electromagnetic field (PEMF) therapy presents several potential advantages including non‐invasiveness, safety, lack of toxicity for non‐cancerous cells, and the possibility of being combined with other available therapies. Indeed, PEMF stimulation has already been used in the context of various cancer types including skin, breast, prostate, hepatocellular, lung, ovarian, pancreatic, bladder, thyroid, and colon cancer in vitro and in vivo. At present, only limited application of PEMF in cancer has been documented in humans. In this article, we review the experimental and clinical evidence of PEMF therapy discussing future perspectives in its use in oncology. Abstract : Pre‐clinical studies show therapeutic efficacy of PEMFs in oncology